Communication with children and adolescents about the diagnosis of a life-threatening condition in their parent. Issue 10176 (16th March 2019) - ,; Betancourt, Theresa; Bluebond-Langner, Myra; D'Souza, Catherine; Fazel, Mina; Fredman-Stein, Kim; Harrop, Emily; Hochhauser, Daniel; Kolucki, Barbara; Lowney, Aoife C; Netsi, Elena; Richter, Linda; et al.
Summary: Many adults diagnosed with a life-threatening condition have children living at home; they and their partners face the dual challenge of coping with the diagnosis while trying to maintain a parenting role. Parents are often uncertain about how, when, and what to tell their children about the condition, and are fearful of the effect on their family. There is evidence that children are often aware that something is seriously wrong and want honest information. Health-care professionals have a key role in supporting and guiding parents and caregivers to communicate with their children about the diagnosis. However, the practical and emotional challenges of communicating with families are compounded by a scarcity of evidence-based guidelines. This Review considers children's awareness and understanding of their parents' condition, the effect of communication around parental life-threatening condition on their wellbeing, factors that influence communication, and the challenges to achieving effective communication. Children's and parents' preferences about communication are outlined. An expert workshop was convened to generate principles for health-care professionals, intended as practical guidance in the current absence of empirically derived guidelines.